Proteção da cultura ou proteção dos animais? uma análise da farra do boi à luz da máxima da proporcionalidade e da jurisprudência do STF - Rangel, Helano Márcio Vieira (2007)
The ox spree is a cultural manifestation displayed in coastal cities of Santa Catarina state, which origins is linked to tauromachy habits of Portuguese and Azorean colonizers. lt consists in releasing and provoking the ox in the most various ways, which goes from physical to psychic harassment, in arder to chase it until the complete exhaustion, occasion when the ox is sacrificed and its meat is shared amongst the carousers. As far as methodology is concerned, the research is applied, quanti-qualitative, explicative and it was built from documental and bibliographical analysis. The present dissertation analyzes the emblematic case of the ox spree, especially concerning the jurídica( dilemma consolidated in the conflict between precepts of fundamental rights, that is, the protection of the cultural heritage in contrast to the protection of the animais. Thus, there is a conflict between two precepts of fundamental rights concerning environmental subject, which have the jurídica( structure of principie and characterize themselves by the prima facie feature and wide factual support. Before the referred concrete collision, the research searches for an adjustment of the goods and values by means of balancing the norms involved, which is a rational method shaped on the maxim of proportionality that determines the precedence of a principie in the face of other. At first, the study analyzes the ethnographic concept of culture and the Brazilian sociocultural constitution, as well as the legal and constitutional protection of culture and cultural heritage, by the means of interpreting the article 215 and 216 of the Federal Constitution. lt still examines the cultural heritage and its defense according to the lnternational Law. Afterwards, the dissertation focuses the concept of animais, the historical evolution of the relation between man and the other animais, the scientific paragons and its correlation with the treatment rendered to animais, as well as the ethical theories linked to animal protection. The work focuses the animal protection law in countries like England, France, Germany, as well as it makes incursions into the International Law applied to the theme. The work still analyzes the constitutional meaning of cruelty and the juridical regime of the animal protection inserted in the article 225, § 1 º, VII of the Federal Constitution. ln the third part, the dissertation examines the constitution and development of tauromachy throughout the history and in various civilizations, as the rituais to Mithra in Ancient Persia nad the myths of Minotaur in ancient Greece. The work still analyzes the tauromachy in the world, Iberian Península, Azares and its arrival in Santa Catarina state, brought by the Azorean colonizers. At that point, the ox spree is addressed under a historical, psychological and anthropological perspective, from the beginning up to the repercussions in the media and amongst environmentalist groups from 1987 onwards. It still discusses the Law nº 9.605/98, which is about the environmental crimes and the paradigmatic decision of the Suprem e Court of Justice about the ox spree. ln like manner, others court decisions on the event are examined. The dissertation concludes that the ox spree is an unconstitutional practice, once the violence against the animais involved in the habit causes the precedence of the animal protection constitutional norm over the cultural protection constitutional norm.